Lead in the marine environment : proceedings of the International Experts Discussion on Lead Occurrence, Fate, and Pollution in the Marine Environment, Rovinj, Yugoslavia, 18-22 October 1977 - Branica, Marko; Konrad, Zdenka (Pergamon Press, 1980)
Lead in the Marine Environment covers the proceedings of the International Experts Discussion on Lead Occurrence, Fate, and Pollution in the Marine Environment, held in Rovinj, Yugoslavia on October 18-22, 1977. The book focuses on the release of lead to the environment, including the techniques, processes, and technologies involved in the analysis of lead in marine ecosystems. The selection first highlights the impact of human on coastal marine ecosystems; analysis of natural and industrial lead in marine ecosystems; and the occurrence of lead in Northeast Pacific and the effects of anthropog.